العوامل المؤثرة في رفع مستوى إقبال الطلاب نحو التعليم المهني والتقني ودور وزارة التربية والتعليم في إقليم الضفة الغربية-فلسطين - صفاء عمر مرشد عمرو
This study examined the factors affecting the level of students' interest in vocational and technical education and the role of the Ministry of Education in the West Bank region - Palestine. This study aimed to explore the impact of financial support in raising the level of students' interest in vocational and technical education; Identifying the impact of the facilities provided in raising the level of students' interest in vocational and technical education in the West Bank in Palestine; And revealing the relationship between society's view of vocational and technical education and the level of student turnout in the West Bank in Palestine; It also aimed to identify the relationship between the majors and programs offered and the level of students' demand for vocational and technical education in the West Bank in Palestine; And to know the relationship between follow-up and comprehensive evaluation of vocational education outcomes and the level of student turnout in the West Bank in Palestine. In order to achieve the objectives of the study, the descriptive analytical method was applied. The study population may consist of three groups. The first is all employees of the General Department of Vocational Education in the Ministry of Education; The second group is all principals and teachers of vocational schools; The third group is in the heads of the approved professional and industrial unions. Stratified random sampling was applied. The data was analyzed using (SPSS) and (Smart-PL3) packages. The study reached a number of results, the most important of which is that the Palestinian Ministry of Education provides the necessary material and technical support for vocational and technical education institutions; Vocational and technical education institutions provide facilities for students to reduce the difficulty of adaptation when transitioning from regular education to vocational training; Vocational and technical education institutions also work to improve students' and society's view of vocational and technical education; Vocational and technical education institutions also offer specializations and programs suitable for the Palestinian labor market; Finally, vocational and technical education institutions undertake a comprehensive follow-up and evaluation of the outputs of vocational education. The study recommended the necessity of guiding professional and craft work from the primary stages by raising topics related to manual work such as agriculture, industry and other crafts; And by increasing the contribution of teachers to the preparation of vocational education curricula because of their expertise and the most important experiences and skills that students should acquire; Finally, the adoption of vocational education and technology as a basic subject within the study plan in the stage of basic learning